Mystical Terms in Johannes Altenstaig's Vocabularius theologiae (1517) - Dubbelman, Samuel J. ca. 20./21. Jh. (Renaissance and reformation, 2024)
This article contributes to the study of Christian mysticism in the sixteenth century by providing translations of mystical terms from Johannes Altenstaig's Vocabularius theologiae (1517), including extasis, devotio, contemplatio, meditatio, mysticum, orare/oratio, raptus, theologia mystica, and unio. The introduction offers an overview of Altenstaig's biography and the theological dictionary and highlights the significance of compilations, particularly those intended for student use, in reconstructing the fundamental characteristics of mystical theology on the eve of the Reformation. The notes to the translations provide a detailed analysis of the sources used by Altenstaig, suggesting the frequent use of recent compilations rather than the original classical texts.